What have we done - Finlay, Alex (Minotaur Books, 2023)
"In one of the year's most anticipated thrillers #1 New York Times bestseller Sarah Pekkanen calls "Alex Finlay's best yet," What Have We Done is a tale about the lives we leave behind and the secrets we carry with us forever. A stay-at-home mom with a past. A has-been rock star with a habit. A reality TV producer with a debt. Three disparate lives. One deadly secret. Twenty five years ago, Jenna, Donnie, and Nico were the best of friends, a bond forged as residents of Savior House, an abusive group home for parentless teens. When the home was shut down--after the disappearance of several kids--the three were split up. Though the trauma of their childhood has never left them, each went on to live successful, if troubled, lives. They haven't seen one another since they were teens but now are reunited for a single haunting reason: someone is trying to kill them. To save their lives, the group will have to revisit the nightmares of their childhoods and confront their past--a past that holds the secret to why someone wants them dead. It's a reunion none of them asked for ... or wanted. But it may be the only way to save all their lives. What Have We Done is both an edge-of-your seat thriller and a gut-wrenching coming-of-age story. And it cements Alex Finlay as one of the new leading voices in thrillers today"--